2012
DOI: 10.7863/jum.2012.31.9.1375
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sonography for Evaluation of the Cervical and Thoracic Esophagus in Children

Abstract: Objectives The purpose of this study was to determine the normal sonographic appearance of the cervical and thoracic esophagus and to provide corresponding measurements in healthy children. Methods In this prospective study, 93 children (51 girls and 42 boys) 1 to 15 years of age were examined sonographically. With the patient in a supine position for evaluation of the cervical esophagus, the ultrasound transducer was placed on both sides of the trachea. To evaluate the thoracic esophagus, the hands were raise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Research revealed that, unlike the thoracic esophagus, the proximal esophagus could easily be assessed by ultrasound, and although the length of the cervical esophagus increased with age, the mean thickness of the cervical esophagus remained constant throughout the age. It was concluded that conventional ultrasound could be easily used to assess proximal esophageal diseases in children (25). In this study, the evaluated indices, including diameter, wall thickness, length, and percentage of dispensability changes after drinking water, in the cervical and abdominal esophagus, were measured by ultrasound, and we evaluated the diagnostic value of ultrasound findings in children with EoE.…”
Section: Discussionmentioning
confidence: 99%
“…Research revealed that, unlike the thoracic esophagus, the proximal esophagus could easily be assessed by ultrasound, and although the length of the cervical esophagus increased with age, the mean thickness of the cervical esophagus remained constant throughout the age. It was concluded that conventional ultrasound could be easily used to assess proximal esophageal diseases in children (25). In this study, the evaluated indices, including diameter, wall thickness, length, and percentage of dispensability changes after drinking water, in the cervical and abdominal esophagus, were measured by ultrasound, and we evaluated the diagnostic value of ultrasound findings in children with EoE.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Esophageal CT demonstrated an increase in thickness between adults with esophageal cancer (6.4 mm) compared to controls (6.0 mm) and to highlighted differences between adults with esophagitis (4.7 mm) and controls (2.9 mm). [ 8 9 ] External sonography performed in 93 children aged 1–15 years determined that the cervical esophagus TWT was 2.8 mm at all ages[ 10 ] and in another group of 124 healthy children 2 days to 12 years the gastroesophageal junction TWT ranged from 2.4 to 5.7 mm. [ 11 ] A previous EUS study of 24 EoE patients, available only as an abstract, has also noted an increased TWT compared to gastroesophageal reflux (GERD) patients (3.86 vs .…”
Section: Introductionmentioning
confidence: 99%